Five-year Survival Data on the Role of Endoscopic Endonasal Nasopharyngectomy in Advanced Recurrent rT3 and rT4 Nasopharyngeal Carcinoma. (March 2020) - Wong, Eugene Hung Chih; Liew, Yew Toong; Loong, Siow Ping; Prepageran, Narayanan
Aim: Endoscopic endonasal nasopharyngectomy (EEN) for recurrent nasopharyngeal carcinoma (rNPC) is being increasingly used due to the added high magnification, reduced morbidities associated with open procedures and good survival outcomes. Most studies looked at usage of EEN in patients with lower recurrent staging (rT1 and rT2) although more and more surgeons are studying the outcome of EEN in advanced rNPC (rT3 and rT4). The aims of this study were to report the long-term 5-year survival outcome of EEN performed in patients with advanced rNPC, and to determine any prognostic factors for patients' survival. Methods: All patients who underwent EEN for advanced rNPC between January 2003 and December 2015 inclusive were analyzed. All surgeries were performed in University Malaya Medical Centre in Kuala Lumpur and Queen Elizabeth Hospital in Sabah. We reported the 5-year overall survival (OS), disease-free survival (DFS) and disease-specific survival (DSS) and any related complications and significant prognostic factors. Results: Twelve patients with rNPC (2 rT3 and 10 rT4) were followed-up over a mean duration of 44.8 months (range, 40-440 weeks). The 5-year OS was 50.0% (mean 44.75 months), DFS was 25.0% (mean 35.25 months) and the DSS was 58.3% (mean 43.33 months). No severe operative complications were encountered and no independent prognostic factors for survival outcome were identified. Conclusion: This is the first report in English that exclusively described the long-term 5-year survival data in patients with both rT3 and rT4 recurrent NPC after EEN. The data suggest that EEN is a feasible treatment to improve survival with minimal morbidities in patients with rT3 and rT4 recurrent NPC. However, more studies with larger patient size is recommended.